Evaluation of antinociceptive activity of nanoliposome-encapsulated and free-form diclofenac in rats and mice - Goh, Jun Zheng; Tang, Sook Nai; Chiong, Hoe Siong; Yong, Yoke Keong; Ahmad, Zuraini; Abdullah, Muhammad Nazrul Hakim (Dove Medical Press, 2015)
Diclofenac is a nonsteroidal anti-inflammatory drug (NSAID) that exhibits anti-inflammatory, antinociceptive, and antipyretic activities. Liposomes have been shown to improve the therapeutic efficacy of encapsulated drugs. The present study was conducted to compare the antinociceptive properties between liposome-encapsulated and free-form diclofenac in vivo via different nociceptive assay models. Liposome-encapsulated diclofenac was prepared using the commercialized proliposome method. Antinociceptive effects of liposome-encapsulated and free-form diclofenac were evaluated using formalin test, acetic acid-induced abdominal writhing test, Randall–Selitto paw pressure test, and plantar test. The results of the writhing test showed a significant reduction of abdominal constriction in all treatment groups in a dose-dependent manner. The 20 mg/kg liposome-encapsulated diclofenac demonstrated the highest antinociceptive effect at 78.97% compared with 55.89% in the free-form group at equivalent dosage. Both liposome-encapsulated and free-form diclofenac produced significant results in the late phase of formalin assay at a dose of 20 mg/kg, with antinociception percentages of 78.84% and 60.71%, respectively. Significant results of antinociception were also observed in both hyperalgesia assays. For Randall–Sellito assay, the highest antinociception effect of 71.38% was achieved with 20 mg/kg liposome-encapsulated diclofenac, while the lowest antinociceptive effect of 17.32% was recorded with 0 mg/kg liposome formulation, whereas in the plantar test, the highest antinociceptive effect was achieved at 56.7% with 20 mg/kg liposome-encapsulated diclofenac, and the lowest effect was shown with 0 mg/kg liposome formulation of 8.89%. The present study suggests that liposome-encapsulated diclofenac exhibits higher antinociceptive efficacy in a dose-dependent manner in comparison with free-form diclofenac.